Clinical spectrum and outcomes of pediatric diphtheria - Herry D. Nawing; Ninny Meutia Pelupessy; Herniati Alimadong; Husein Albar (Indonesian Pediatric Society, 2019)
Background Although vaccination programs have succeeded in reducing the incidence of diphtheria, it remains a health problem in Asia, including Indonesia. Objective To investigate the clinical spectrum and outcomes of pediatric diphtheria in Wahidin Sudirohusodo Hospital. Methods This study was a retrospective review of childhood diphtheria medical records from January 2011 to December 2017 in Wahidin Sudirohusodo Hospital, Makassar, South Sulawesi. Recorded data consisted of age, gender, nutritional and immunization statuses, signs and symptoms, throat swab culture results, complications, and outcomes. Results Of 28 subjects aged 9 months to 17.10 years, the majority were >5 years (57.1%) and male (60.7%). Subjects’ mean age was 6.15 years and 82.1% of cases were well nourished. Overall, 85.7% had received complete immunizations, while 14.3% were not immunized, having received neither basic nor booster vaccines. The presenting manifestations were fever, pseudomembranes, and sore throat in all subjects, enlarged tonsils (78.57%), dysphagia (67.86%), cough (57.14%), headache (57.14%), hoarseness (67.86%), bull neck (25%), and myocarditis (14.3%). Most subjects had hospital stays of >10 days (67.9%). Mortality was 14.3%, usually in those admitted with a late, deteriorating condition and dying before getting optimal treatment. Poor outcome was significantly associated with the lack of basic or booster immunizations, poor nourishment, bull neck, myocarditis, and hospital stays < 5 days (P<0.05 for all). Conclusion The clinical spectrum and outcomes of pediatric diphtheria in this study are relatively similar to reports from other hospitals. Mortality was mostly in patients who lack basic or booster immunizations, are poorly nourished, or have bull neck, myocarditis, or hospital stays < 5 days.